The developmental process of suicidal ideation among adolescents: social and psychological impact from a nation-wide survey - Antonio Tintori; Maurizio Pompili; Giulia Ciancimino; Gianni Corsetti; Loredana Cerbara (Scientific Reports, 2023)
Abstract Suicidal ideation is a multifactorial phenomenon that is increasingly prevalent among adolescents, especially following the impact of Covid 19 pandemic on their mental health. Its analysis necessitates an interdisciplinary approach that simultaneously considers sociological and psychological perspectives, especially looking at the role of interpersonal relationships and structural inequalities. The present study, based on a face-to-face survey conducted with a representative sample of 4288 adolescents, aims to identify the factors that most differentiate individuals with and without suicidal ideation, proposing a descriptive model of development process of this phenomenon with reference to the Italian context. We analysed variables related to socio-demographic status, relational status, social interactions, and psychological well-being using multiple correspondence analysis and logistic regression models. The results provide evidence for the existence of a direct association between negative psychological status and suicidal ideation but clarify that the psychological aspects are associated with sociodemographic characteristics and have their origins in the social sphere.